Effect of a participatory multisectoral maternal and newborn intervention on maternal health service utilization and newborn care practices: a quasi-experimental study in three rural Ugandan districts. (1st August 2017) - Ekirapa-Kiracho, Elizabeth; Muhumuza Kananura, Rornald; Tetui, Moses; Namazzi, Gertrude; Mutebi, Aloysius; George, Asha; Paina, Ligia; Waiswa, Peter; Bumba, Ahmed; Mulekwa, Godfrey; Nakiganda-Busiku, Dinah; Lyagoba, Moses; et al.
ABSTRACT: Background : The MANIFEST study in eastern Uganda employed a participatory multisectoral approach to reduce barriers to access to maternal and newborn care services. Objectives : This study analyses the effect of the intervention on the utilization of maternal and newborn services and care practices. Methods : The quasi-experimental pre- and post-comparison design had two main components: community mobilization and empowerment, and health provider capacity building. The primary outcomes were utilization of antenatal care (ANC), delivery and postnatal care, and newborn care practices. Baseline ( n  = 2237) and endline ( n  = 1946) data were collected from women of reproductive age. The  data was analysed using difference in differences (DiD) analysis and  logistic regression. Results : The DiD results revealed an 8% difference in early ANC attendance ( p  < 0.01) and facility delivery ( p  < 0.01). Facility delivery increased from 66% to 73% in the intervention area, but remained unchanged in the comparison area (64% vs 63%, p  < 0.01). The DiD results also demonstrated a 20% difference in clean cord care ( p  < 0.001) and an 8% difference in delayed bathing ( p  < 0.001). The intervention elements that predicted facility delivery were attending ANC four times [adjusted odds ratio (aOR) 1.42, 95% confidence interval (CI) 1.17–1.74] and saving for maternal health (aOR 2.11, 95% CI 1.39–3.21). Facility delivery and village health team (VHT) home visits were key predictors for clean cord care and skin-to-skin care. Conclusions : The multisectoral approach had positive effects on early ANC attendance, facility deliveries and newborn care practices. Community resources such as VHTs and savings are crucial to maternal and newborn outcomes and should be supported. VHT-led health education should incorporate practical measures that enable families to save and access transport services to enhance adequate preparation for birth.